Hollow carbon sphere with porous structure as well as preparation method and application of hollow carbon sphere

By using polypolyphenols and their derivatives and hard template methods to prepare hollow carbon balls, the problems of complexity and contamination of the preparation of three-dimensional spherical structure electrochemical catalysts in the prior art are solved, and hollow carbon with high specific surface area and good electrochemical properties are achieved Ball preparation.

CN119425655APending Publication Date: 2025-02-14SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411144791.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art When preparing electrochemical catalysts with three-dimensional spherical structures, multiple steps and template removal processes are required, resulting in environmental pollution and preparation complexity.

Method used

Polypolyphenols and their derivatives are used as precursors, and the precursor morphology is supported by the hard template method, and hollow carbon spheres with pores are formed at high temperature by internal pressure method, and electrochemical catalysts with multi-stage pore structure are obtained directly through carbonization.

Benefits of technology

The preparation of hollow carbon spheres with a large specific surface area and rich multi-stage pore structure was achieved, with good electrochemical properties, and the preparation process was simplified to avoid environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425655A_ABST
    Figure CN119425655A_ABST
Patent Text Reader

Abstract

The invention relates to a hollow carbon sphere with a porous structure as well as a preparation method and application of the hollow carbon sphere. The invention relates to a preparation method of hollow carbon spheres with porous structures, which comprises the following steps: dispersing a hard template in a buffer solution, adding polyphenol and derivatives thereof, and carrying out polymerization reaction; and after the reaction is finished, carrying out centrifugal washing, drying and grinding on the reaction solution, and carbonizing under an inert gas condition to obtain the hollow carbon spheres. According to the preparation method of the hollow carbon sphere with the porous structure, the precursor morphology is supported by a hard template method, pores are formed at a high temperature through an internal pressure method, and an electrochemical catalyst with the hollow carbon sphere with the multi-stage porous structure or bowl-shaped carbon sphere can be obtained only through carbonization. The catalyst has a relatively large specific surface area, a rich multi-stage pore structure and relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical catalysts, and specifically relates to a hollow carbon sphere with a porous structure and a preparation method and application thereof. Background Art

[0002] Energy and environment have always been topics of great concern at home and abroad. Limited fossil fuel energy, increasingly serious environmental pollution problems, and the production and living needs of a large population have forced us to make updates and changes as soon as possible. The development of efficient, green and environmentally friendly new energy to replace traditional fossil fuels has become an important direction of development today. The widespread application of new energy sources urgently requires researchers to develop efficient catalysts to reduce reaction potential energy and enhance reaction kinetics. Common electrochemical catalysts include carbon-based catalysts, metal-based catalysts, and organic polymer-based catalysts. Among them, carbon-based catalysts have a wide range of sources and diverse morphologies and are recognized by many. Because carbon-based catalysts can be synthesized by pyrolysis of different carbon sources, such as metal-organic framework materials, template self-assembled soft and hard nanomaterials, and natural biomass or agricultural waste containing cellulose, hemicellulose and lignin. Among them, MN X The catalyst with -C structure as the carrier is the most perfect, and this structure is conducive to the adsorption of gas during the electrochemical reaction.

[0003] The morphology of the catalyst also has a certain influence on its catalytic performance. The one-dimensional structure has good conductivity, but it is very easy to stack and aggregate with each other, resulting in the active sites being covered and unable to exert the expected catalytic performance. The two-dimensional structure can carry a large number of active sites and has a high specific surface area, but it can easily cover each other, and the method of controlling its thickness has always been relatively complicated. Studies have found that three-dimensional structures, especially spherical structures, have good dispersibility and can avoid catalyst stacking. Designing them into hollow structures can also expose a large number of active sites while increasing the specific surface area. However, the corresponding preparation method is relatively complicated and requires a multi-step process. Usually, the formation of the structure requires a template support structure, and the subsequent removal of the template requires strong acid or strong alkali, which pollutes the environment and goes against the original intention of green environmental protection.

[0004] Polyphenols and their derivatives are a kind of biomass active precursors of porous carbon materials that can be developed sustainably. Their unique adhesion advantages and rich surface functional groups give them hydrophilicity, conductivity and other characteristics, enabling them to modify the precursors to the greatest extent. In addition, polyphenols and their derivatives can complex with a variety of metals, anchor metals to make them single atoms or clusters, and can completely replicate the template morphology after carbonization. Studies have shown that they have a high carbonization yield and are easy to form amorphous carbon. This method can be used to prepare a variety of electrochemical catalysts derived from metal templates. The auxiliary strategy of polyphenols and their derivatives can not only prepare high-performance composite supercapacitors, but also prepare porous carbon materials that are different from conventional ones, which greatly breaks the limitation of carbon materials that affect their electrochemical properties due to their surface morphology and chemical structure.

[0005] In view of this, the present invention proposes a novel hollow carbon sphere with a porous structure and a preparation method thereof. The preparation method is simple and does not require additional processing of a hard template, and can obtain hollow carbon spheres with a larger specific surface area and better electrochemical properties. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing hollow carbon spheres with a porous structure. Polyphenols and their derivatives are used as precursors, and the precursor morphology is supported by a hard template method to form porous hollow carbon spheres by an internal pressure method at high temperature. An electrochemical catalyst of hollow carbon spheres or bowl-shaped carbon spheres with a multi-level porous structure can be obtained only by carbonization.

[0007] In order to achieve the above purpose, the technical solution adopted is:

[0008] A method for preparing a hollow carbon sphere with a porous structure comprises the following steps:

[0009] After dispersing the hard template in a buffer solution, polyphenols and their derivatives are added to carry out polymerization reaction;

[0010] After the reaction is completed, the reaction solution is centrifugally washed, dried, ground, and then carbonized under inert gas conditions to obtain the hollow carbon spheres.

[0011] Furthermore, the buffer solution is a Tris-HCl buffer solution with a pH of 8.5;

[0012] The hard film plate is a ZnO ball, a polystyrene ball, or a PMMA ball;

[0013] The polyphenols and their derivatives are tannic acid, gallic acid, dopamine, pyrogallol, or EGCG.

[0014] Furthermore, the molar volume ratio of the polyphenols and their derivatives to the buffer solution is 2-2.5 mol:1L.

[0015] Furthermore, the polymerization reaction time is 20-24h;

[0016] The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 2-3h.

[0017] Furthermore, the polymerization reaction time is 24h;

[0018] The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 3 hours.

[0019] Another object of the present invention is to provide a hollow carbon sphere with a porous structure, which is produced by the above-mentioned preparation method. The catalyst has a large specific surface area, a rich multi-level pore structure and good electrochemical performance.

[0020] Another object of the present invention is to provide application of the hollow carbon spheres in electrochemistry.

[0021] In order to achieve the above purpose, the technical solution adopted is:

[0022] The above-mentioned hollow carbon spheres are used in electrochemistry.

[0023] Furthermore, the hollow carbon spheres are used to prepare an electrochemical ink-coated glassy carbon electrode, the steps of which are:

[0024] The hollow carbon spheres are dispersed in anhydrous ethanol, and Nafion solution is added. After being evenly dispersed by ultrasonication, the hollow carbon spheres are coated on a glassy carbon electrode and dried naturally.

[0025] Furthermore, the mass volume ratio of the anhydrous ethanol, the hollow carbon spheres, and the 25wt% Nafion solution is 500-700μL:1mg:30μL.

[0026] Furthermore, the mass volume ratio of the anhydrous ethanol, the hollow carbon spheres, and the 25wt% Nafion solution is 600μL:1mg:30μL.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The technical solution of the present invention has a green and environmentally friendly preparation process, abandons the subsequent template removal process of the traditional hard template method, and simplifies the experimental steps.

[0029] 2. The technical solution of the present invention, based on the selection of ZnO beads, polystyrene beads, and PMMA beads, uses the internal pressure method to cause the sample to produce a porous structure, defects, and even explode to form a bowl-shaped structure, providing analytical characterization for the thermal decomposition process of the corresponding hard template.

[0030] 3. The technical solution of the present invention has a large specific surface area, the minimum of which is not less than 200m 2 / g, up to 1100m 2 / g, with a stable and rich multi-level pore structure, good conductivity and low resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The following are scanning electron microscope images of samples in Examples 1-4: a. Example 1; b. Example 2; c. Example 3; d. Example 4.

[0032] Figure 2 The electron microscope images of the sample of Comparative Example 1. a. Scanning image; b. Transmission image.

[0033] Figure 3 This is the electron microscope image of the sample of Comparative Example 2.

[0034] Figure 4 The electrochemical performance data of the samples in Examples 1-2 and Comparative Example 2.

[0035] Figure 5 The electrochemical performance data of the samples in Examples 3-4.

[0036] Figure 6 This is the N2 adsorption-desorption curve of the sample in Example 1.

[0037] Figure 7 This is the N2 adsorption-desorption curve of the sample in Example 3.

[0038] Figure 8 This is the N2 adsorption-desorption curve of the sample in Comparative Example 2. DETAILED DESCRIPTION

[0039] In order to further illustrate the present invention's porous structured hollow carbon spheres and their preparation methods and applications, and to achieve the intended purpose of the invention, the following is a detailed description of the present invention's porous structured hollow carbon spheres and their preparation methods and applications, their specific implementation methods, structures, features and their effects, in combination with preferred embodiments. In the following description, different "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0040] The following will further introduce in detail the porous structure of the hollow carbon sphere and its preparation method and application in combination with specific embodiments of the present invention:

[0041] The present invention discloses a porous hollow carbon sphere and its preparation method and application. Polyphenol and its derivatives are used as precursors. The carbon sphere is formed into a rich pore structure or even a bowl-shaped structure through high-temperature carbonization and internal template evaporation. The carbon sphere prepared by the method has the advantages of large specific surface area, rich pore structure, and many surface defects. The carbon material is coated on a glassy carbon electrode and tested by electrochemical cyclic voltammetry. The material has an excellent catalytic effect on the electrochemical reaction.

[0042] The technical solution of the present invention is:

[0043] A method for preparing a hollow carbon sphere with a porous structure comprises the following steps:

[0044] After dispersing the hard template in a buffer solution, polyphenols and their derivatives are added to carry out polymerization reaction;

[0045] After the reaction is completed, the reaction solution is centrifugally washed, dried, ground, and then carbonized under inert gas conditions to obtain the hollow carbon spheres.

[0046] Preferably, the buffer solution is a Tris-HCl buffer solution with a pH of 8.5;

[0047] The hard film plate is a ZnO ball, a polystyrene ball, or a PMMA ball, etc.;

[0048] The polyphenols and their derivatives are tannic acid, gallic acid, dopamine, pyrogallol or EGCG (tea polyphenols), etc., but are not limited thereto.

[0049] In the above technical scheme, ZnO beads, polystyrene beads or PMMA beads are selected as templates, which can be directly evaporated during the carbonization process, causing the product to produce pore structures, defects and even explode to form a bowl-shaped structure, so that the hollow carbon spheres obtain structures such as multi-level pores and have a high specific surface area, thus having a stable and rich multi-level pore structure, good conductivity and low resistance; at the same time, the subsequent template removal treatment is avoided.

[0050] The ZnO beads, polystyrene beads or PMMA beads can be prepared into spherical hard templates by conventional methods in the art.

[0051] Preferably, the molar volume ratio of the polyphenols and their derivatives to the buffer solution is 2-2.5 mol:1L.

[0052] Preferably, the polymerization reaction time is 20-24h;

[0053] The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 2-3h.

[0054] Further preferably, the polymerization reaction time is 24h;

[0055] The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 3 hours.

[0056] A hollow carbon sphere with a porous structure is produced by the above-mentioned preparation method. The catalyst has a large specific surface area, a rich multi-level pore structure and good electrochemical performance.

[0057] The above-mentioned hollow carbon spheres are used in electrochemistry.

[0058] Preferably, the hollow carbon spheres are used to prepare an electrochemical ink-coated glassy carbon electrode, the steps of which are:

[0059] The hollow carbon spheres are dispersed in anhydrous ethanol, and Nafion solution is added. After being evenly dispersed by ultrasonication, the hollow carbon spheres are coated on a glassy carbon electrode and dried naturally.

[0060] Further preferably, the mass volume ratio of the anhydrous ethanol, the hollow carbon spheres, and the 25wt% Nafion solution is 500-700 μL:1 mg:30 μL.

[0061] Further preferably, the mass volume ratio of the anhydrous ethanol, the hollow carbon spheres, and the 25wt% Nafion solution is 600 μL:1 mg:30 μL.

[0062] Example 1.

[0063] The specific steps are as follows:

[0064] A Preparation of carbon materials:

[0065] (1) Weigh 25 mmol of zinc acetate and dissolve it in deionized water, then add TEA, stir mechanically for 2 hours, transfer it to a polytetrafluoroethylene kettle for hydrothermal reaction, react at 160° C. for 2 hours, cool it to room temperature, centrifuge and wash it several times, collect it, and dry it in an oven at 50° C. to obtain a ZnO spherical hard template.

[0066] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0067] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0068] (4) Dry the centrifuged sample and grind it after drying.

[0069] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 900°C at a heating rate of 1°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0070] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0071] (1) Disperse 1 mg of the carbon material obtained in step A in 600 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0072] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0073] C Electrochemical performance test:

[0074] The electrochemical detection equipment consists of an electrochemical workstation, a reaction cell, a working electrode, a counter electrode and a reference electrode; a platinum wire is used as a counter electrode, silver / silver chloride is used as a reference electrode, and the working electrode is a sample-modified glassy carbon electrode; cyclic voltammetry is used, with a scanning potential of 50mV / s and a scanning range X of 0-1.4V.

[0075] Example 2.

[0076] The specific steps are as follows:

[0077] A Preparation of carbon materials:

[0078] (1) Weigh 25 mmol of zinc acetate and dissolve it in deionized water, then add TEA, stir mechanically for 2 hours, transfer it to a polytetrafluoroethylene kettle for hydrothermal reaction, react at 160° C. for 2 hours, cool it to room temperature, centrifuge and wash it several times, collect it, and dry it in an oven at 50° C. to obtain a ZnO spherical hard template.

[0079] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0080] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0081] (4) Dry the centrifuged sample and grind it after drying.

[0082] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 900°C at a heating rate of 5°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0083] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0084] (1) Disperse 1 mg of the carbon material obtained in step A in 600 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0085] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0086] C Electrochemical performance test:

[0087] The electrochemical detection equipment consists of an electrochemical workstation, a reaction cell, a working electrode, a counter electrode and a reference electrode; a platinum wire is used as a counter electrode, silver / silver chloride is used as a reference electrode, and the working electrode is a sample-modified glassy carbon electrode; cyclic voltammetry is used, with a scanning potential of 50mV / s and a scanning range X of 0-1.4V.

[0088] Example 3.

[0089] The specific steps are as follows:

[0090] A Preparation of carbon materials:

[0091] (1) Under an inert gas atmosphere, 12 mL of monomer polystyrene was added to a four-necked flask filled with deionized water and gradually heated to 75°C, followed by addition of an aqueous solution of potassium persulfate and reacted for 24 hours. The solution was cooled, centrifuged, washed, dried, and collected to obtain a polystyrene spherical template.

[0092] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2.5 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0093] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0094] (4) Dry the centrifuged sample and grind it after drying.

[0095] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 800°C at a heating rate of 1°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0096] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0097] (1) Disperse 1 mg of the carbon material obtained in step A in 500 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0098] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0099] C Electrochemical performance test:

[0100] The electrochemical detection equipment consists of an electrochemical workstation, a reaction cell, a working electrode, a counter electrode and a reference electrode; a platinum wire is used as a counter electrode, silver / silver chloride is used as a reference electrode, and the working electrode is a sample-modified glassy carbon electrode; cyclic voltammetry is used, with a scanning potential of 100 mV / s and a scanning range X of -1.2-0.2V.

[0101] Example 4.

[0102] The specific steps are as follows:

[0103] A Preparation of carbon materials:

[0104] (1) Under an inert gas atmosphere, 12 mL of monomer polystyrene was added to a four-necked flask filled with deionized water and gradually heated to 75°C, followed by addition of an aqueous solution of potassium persulfate and reacted for 24 hours. The solution was cooled, centrifuged, washed, dried, and collected to obtain a polystyrene spherical template.

[0105] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2.5 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0106] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0107] (4) Dry the centrifuged sample and grind it after drying.

[0108] (5) The ground sample was placed in a tubular furnace under inert gas protection, and the temperature was raised to 800°C at a heating rate of 5°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0109] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0110] (1) Disperse 1 mg of the carbon material obtained in step A in 500 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0111] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0112] C Electrochemical performance test:

[0113] The electrochemical detection equipment consists of an electrochemical workstation, a reaction cell, a working electrode, a counter electrode and a reference electrode; a platinum wire is used as a counter electrode, silver / silver chloride is used as a reference electrode, and the working electrode is a sample-modified glassy carbon electrode; cyclic voltammetry is used, with a scanning potential of 100 mV / s and a scanning range X of -1.2-0.2V.

[0114] Example 5.

[0115] A Preparation of carbon materials:

[0116] (1) Prepare PMMA ball template using conventional methods.

[0117] (2) Disperse 0.5 g of PMMA hard template in 250 mL of buffer solution (Tris-HCl buffer solution with pH = 8.5), add tannic acid to the dispersion (the ratio of tannic acid to buffer solution is 2.2 mol:1 L), and allow it to complete a polymerization reaction for 20 hours.

[0118] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0119] (4) Dry the centrifuged sample and grind it after drying.

[0120] (5) The ground sample was placed in a tubular furnace under inert gas protection, and the temperature was raised to 850°C at a heating rate of 3°C / min and kept for 2 hours for carbonization and decomposition to obtain a carbon material.

[0121] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0122] (1) Disperse 1 mg of the carbon material obtained in step A in 500 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0123] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0124] Example 6.

[0125] A Preparation of carbon materials:

[0126] (1) Prepare PMMA ball template using conventional methods.

[0127] (2) Disperse 0.5 g of PMMA hard template in 250 mL of buffer solution (Tris-HCl buffer solution with pH = 8.5), add gallic acid to the dispersion (the ratio of gallic acid to buffer solution is 2.0 mol:1 L), and allow it to complete a polymerization reaction for 22 hours.

[0128] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0129] (4) Dry the centrifuged sample and grind it after drying.

[0130] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 800°C at a heating rate of 4°C / min and kept at that temperature for 2.5 hours for carbonization and decomposition to obtain a carbon material.

[0131] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0132] (1) Disperse 1 mg of the carbon material obtained in step A in 600 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse uniformly by ultrasonication to obtain a dispersion.

[0133] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0134] Example 7.

[0135] A Preparation of carbon materials:

[0136] (1) Weigh 25 mmol of zinc acetate and dissolve it in deionized water, then add TEA, stir mechanically for 2 hours, transfer it to a polytetrafluoroethylene kettle for hydrothermal reaction, react at 160°C for 2 hours, cool it to room temperature, centrifuge and wash it several times, collect it, and dry it in an oven at 50°C to obtain a ZnO spherical hard template.

[0137] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and pyrogallol (the ratio of pyrogallol to buffer solution was 2.4 mol:1 L) was added to the dispersion to complete the polymerization reaction for 21 hours.

[0138] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0139] (4) Dry the centrifuged sample and grind it after drying.

[0140] (5) The ground sample was placed in a tubular furnace under inert gas protection, and the temperature was raised to 880°C at a heating rate of 2°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0141] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0142] (1) Disperse 1 mg of the carbon material obtained in step A in 650 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse evenly by ultrasonication to obtain a dispersion.

[0143] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0144] Example 8.

[0145] A Preparation of carbon materials:

[0146] (1) Under an inert gas atmosphere, 12 mL of monomer polystyrene was added to a four-necked flask filled with deionized water and gradually heated to 75°C, followed by addition of an aqueous solution of potassium persulfate and reacted for 24 hours. The solution was cooled, centrifuged, washed, dried, and collected to obtain a polystyrene spherical template.

[0147] (2) 0.5 g of the hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution at pH = 8.5), and EGCG was added to the dispersion (the ratio of EGCG to the buffer solution was 2.2 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0148] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0149] (4) Dry the centrifuged sample and grind it after drying.

[0150] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 900°C at a heating rate of 4°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0151] B. Preparation of electrochemical ink coated glassy carbon electrode:

[0152] (1) Disperse 1 mg of the carbon material obtained in step A in 650 μL of anhydrous ethanol, add 30 μL of 25 wt% Nafion solution, and disperse evenly by ultrasonication to obtain a dispersion.

[0153] (2) Apply 10 μL of the dispersion onto the glassy carbon electrode and allow to dry naturally.

[0154] Comparative Example 1.

[0155] The specific steps are as follows:

[0156] A Preparation of carbon materials:

[0157] (1) Weigh 25 mmol of zinc acetate and dissolve it in deionized water, then add TEA, stir mechanically for 2 hours, transfer it to a polytetrafluoroethylene kettle for hydrothermal reaction, react at 160° C. for 2 hours, wait for it to cool to room temperature, centrifuge and wash it several times, collect it, and dry it in an oven at 50° C. to obtain a ZnO spherical hard template.

[0158] (2) The hard template was dispersed in 250 mL of a buffer solution (Tris-HCl buffer solution with a pH of 8.5), and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2 mol:1 L), and the polymerization reaction was completed for 24 hours.

[0159] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0160] (4) Dry the centrifuged sample and grind it after drying.

[0161] (5) The ground sample was placed in a tube furnace under inert gas protection, and the temperature was raised to 800°C at a heating rate of 1°C / min and kept at that temperature for 3 hours for carbonization and decomposition to obtain a carbon material.

[0162] The electron microscope scanning image of the carbon material prepared in Comparative Example 1 is as follows Figure 2 As shown in a, it can be seen from the figure that when the ZnO spherical hard template is selected, when the carbonization temperature is too low, the carbon shell surface will be more complete, but lack obvious pore structure, thus affecting the performance. This is caused by incomplete evaporation of the ZnO template. From the electron microscope transmission image of comparative example 1, Figure 2 In b, it can be seen that the ZnO nanoparticles remain in the spherical structure and do not form a complete hollow structure.

[0163] Comparative Example 2.

[0164] The specific steps are as follows:

[0165] A Preparation of carbon materials:

[0166] (1) 6 mL of anhydrous ethanol was added to 45 mL of deionized water, and then 2 mL of ammonia and 0.5 g of CTAB were added. After stirring for 15 min, 1 mL of TEOS was added and reacted for 2 hours. The mixture was washed by centrifugation several times, collected, and dried in an oven at 50 °C to obtain a SiO2 spherical hard template.

[0167] (2) 0.5 g of the hard template was dispersed in 250 mL of buffer solution, and dopamine was added to the dispersion (the ratio of dopamine to buffer solution was 2 mol:1 L), and the polymerization reaction was allowed to complete for 24 hours.

[0168] (3) The sample after the reaction is centrifuged and washed until the washing liquid is clear and transparent.

[0169] (4) Dry the centrifuged sample and grind it after drying.

[0170] (5) The ground sample was placed in a tube furnace under inert gas protection and heated to 900 °C at a rate of 1 °C / min for 3 h for carbonization.

[0171] (6) The carbonized sample was immersed in 4 wt % HF and etched at room temperature for 12 hours to remove the SiO2 template.

[0172] (7) The etched carbon spheres were washed with deionized water until neutral and dried at 50°C.

[0173] The products of Examples 1-4 and Comparative Example 2 were tested.

[0174] (1) Scanning electron microscope

[0175] The scanning electron microscope images of Examples 1-4 are as follows Figure 1 The scanning electron microscope image of Comparative Example 2 is shown in Figure 3 shown.

[0176] Depend on Figure 3 It can be seen that the surface of the material in the figure is rough, the hollow structure has poor support, the morphology is poorly preserved, and an obvious pore structure cannot be directly formed. Figure 1 Obvious pore structure can be observed. Figure 1 (b) and (d) clearly show a bowl-shaped structure. That is, the faster the heating rate, the more obvious the pore structure, and the higher the temperature, the more pores there are.

[0177] (2) Electrochemical performance

[0178] The electrochemical performance data of Examples 1-4 and Comparative Example 2 are as follows: Figure 4-5 As shown. Figure 4 It can be seen that in Examples 1 and 2, as the carbonization temperature and heating rate change, the potential of the oxygen reduction peak in the cyclic voltammetry scanning image also changes, and Example 1 has the highest oxygen reduction peak potential and the widest response area. Examples 3-4 have good responses in supercapacitors. Comparative Example 2 was electrochemically tested under the same carbonization conditions and test conditions as Example 1, but its performance response was poor, which can be judged to be due to the lack of pore structure.

[0179] (3) Specific surface area

[0180] The N2 adsorption and desorption performance data of Example 1 are as follows: Figure 6 As shown, the N2 adsorption and desorption performance data of Example 3 are as follows Figure 7 As shown, the N2 adsorption and desorption performance data of Comparative Example 2 are as follows Figure 8 shown.

[0181] Depend on Figure 6It can be seen that Example 1 has a larger specific surface area and a multi-level pore structure, which is caused by the volatilization of the internal template during the high temperature process. The volatile gas of the hard template overflows from the inside of the shell layer at high temperature, resulting in the pore structure of the shell layer. The excessively fast heating rate generates high pressure to form a bowl-shaped structure. The hard template of Comparative Example 2 is removed by room temperature etching, and no gas overflows during the carbonization process, so it basically has no pore structure.

[0182] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.

Claims

1. A method for preparing a hollow carbon sphere with a porous structure, characterized in that: The following steps are involved: After dispersing the hard template in a buffer solution, polyphenols and their derivatives are added to carry out polymerization reaction; After the reaction is completed, the reaction solution is centrifugally washed, dried, ground, and then carbonized under inert gas conditions to obtain the hollow carbon spheres.

2. The preparation method according to claim 1, characterized in that: The buffer solution is a Tris-HCl buffer solution with a pH of 8.5; The hard film plate is a ZnO ball, a polystyrene ball, or a PMMA ball; The polyphenols and their derivatives are tannic acid, gallic acid, dopamine, pyrogallol, or EGCG.

3. The preparation method according to claim 1, characterized in that: The molar volume ratio of the polyphenols and their derivatives to the buffer solution is 2-2.5 mol:1L.

4. The preparation method according to claim 1, characterized in that: The polymerization reaction time is 20-24h; The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 2-3h.

5. The preparation method according to claim 4, characterized in that: The polymerization reaction time is 24h; The carbonization process is as follows: heating to 800-900°C at a heating rate of 1-5°C / min and keeping the temperature for 3 hours.

6. A hollow carbon sphere with a porous structure, characterized in that: The method is produced by any one of claims 1 to 5.

7. Use of the hollow carbon spheres according to claim 6 in electrochemistry.

8. The use according to claim 7, characterized in that: The hollow carbon spheres are used to prepare electrochemical ink-coated glassy carbon electrodes, and the steps are as follows: The hollow carbon spheres are dispersed in anhydrous ethanol, and Nafion solution is added. After being evenly dispersed by ultrasonication, the hollow carbon spheres are coated on a glassy carbon electrode and dried naturally.

9. The use according to claim 8, characterized in that: The mass volume ratio of the anhydrous ethanol, the hollow carbon spheres and the 25wt% Nafion solution is 500-700μL:1mg:30μL.

10. The use according to claim 9, characterized in that: The mass volume ratio of the anhydrous ethanol, the hollow carbon spheres and the 25wt% Nafion solution is 600μL:1mg:30μL.